Implementing European climate adaptation policy. How local policymakers react to European policy - Hartmann, Thomas; Spit, Tejo (TeMA - Journal of Land Use, Mobility and Environment, 2015)
EU policy and projects have an increasing influence on policymaking for climate adaptation. This is especially evident in the development of new climate adaptation policies in transnational city networks. Until now, climate adaptation literature has paid little attention to the influence that these EU networks have on the adaptive capacity in cities. This paper uses two Dutch cities as an empirical base to evaluate the influence of two EU climate adaptation projects on both the experience of local public officials and the adaptive capacity in the respective cities. The main conclusion is that EU climate adaptation projects do not automatically lead to an increased adaptive capacity in the cities involved. This is due to the political opportunistic use of EU funding, which hampers the implementation of climate adaptation policies. Furthermore, these EU projects draw attention away from local network building focused on the development and implementation of climate adaptation policies. These factors have a negative cumulative impact on the performance of these transnational policy networks at the adaptive capacity level in the cities involved. Therefore, in order to strengthen the adaptive capacity in today’s European cities, a context-specific, integrative approach in urban planning is needed at all spatial levels. Hence, policy entrepreneurs should aim to create linkage between the issues in the transnational city network and the concerns in local politics and local networks.